Opposition to Inbreeding Between Close Kin Reflects Inclusive Fitness Costs - Antfolk, Jan; Lieberman, Debra; Harju, Christopher; Albrecht, Anna; Mokros, Andreas; Santtila, Pekka (Frontiers in Psychology, 2018)
Due to the intense selection pressure against inbreeding, humans are expected to possess psychological adaptations that regulate mate choice and avoid inbreeding. From a gene’s-eye perspective, there is little difference in the evolutionary costs between situations where an individual him/herself is participating in inbreeding and inbreeding among other close relatives. The difference is merely quantitative, as fitness can be compromised via both routes. The question is whether humans are sensitive to the direct as well as indirect costs of inbreeding. Using responses from a large population-based sample (27,364 responses from 2,353 participants), we found that human motivations to avoid inbreeding closely track the theoretical costs of inbreeding as predicted by inclusive-fitness theory. Participants were asked to select in a forced choice paradigm, which of two acts of inbreeding with actual family members they would want to avoid most. We found that the estimated fitness costs explained 83.6% of participant choices. Importantly, fitness costs explained choices also when the self was not involved. We conclude that humans intuit the indirect fitness costs of mating decisions made by close family members and that psychological inbreeding avoidance mechanisms extend beyond self-regulation.